2012
DOI: 10.1002/jbmr.1836
|View full text |Cite
|
Sign up to set email alerts
|

An energetic orphan in an endocrine tissue: A revised perspective of the function of estrogen receptor-related receptor alpha in bone and cartilage

Abstract: Estrogen receptor-related receptor alpha (ERRa) is an orphan nuclear receptor with sequence homology to the estrogen receptors, ERa/ b, but it does not bind estrogen. ERRa not only plays a functional role in osteoblasts but also in osteoclasts and chondrocytes. In addition, the ERRs, including ERRa, can be activated by coactivators such as peroxisome proliferator-activated receptor-gamma coactivator-1 (PGC1a and b) and are implicated in adipogenesis, fatty acid oxidation, and oxidative stress defense, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 99 publications
0
28
0
Order By: Relevance
“…48,49 The estrogen receptor-related receptors have a demonstrated role in promoting VSMC mineralization and bone formation and hence may be prime candidates for further investigation of these pathways with specific antagonist or silencing studies. 50,51 Interestingly, we found that E2 had site-specific effects on both calcification and ERβ expression. E2 increased plaque calcification and decreased ERβ expression in the aortic sinus but not the innominate artery, in both male and female animals.…”
Section: Discussionmentioning
confidence: 75%
“…48,49 The estrogen receptor-related receptors have a demonstrated role in promoting VSMC mineralization and bone formation and hence may be prime candidates for further investigation of these pathways with specific antagonist or silencing studies. 50,51 Interestingly, we found that E2 had site-specific effects on both calcification and ERβ expression. E2 increased plaque calcification and decreased ERβ expression in the aortic sinus but not the innominate artery, in both male and female animals.…”
Section: Discussionmentioning
confidence: 75%
“…We and others demonstrated previously that ERR α modulates ROS production in cancer cells [12, 22, 23]. We next examined whether ERR α -mediated MTX resistance was through control of ROS.…”
Section: Resultsmentioning
confidence: 97%
“…A total of 1,068 genes were induced (>1.5 fold) and 1,445 genes were suppressed (>1.5 fold) in MYC-deficient OCPs compared with control OCPs ( Figure 3A). We used gene set enrichment analysis (GSEA) (25) to broadly test for enrichment of well-defined gene sets from the comprehensive ERRα is not an estrogen receptor, but instead is a nuclear receptor implicated in increasing cellular energy metabolism in tissues such as liver and skeletal muscle in response to environmental challenges that require high energy levels (26)(27)(28). Although ERRα has been implicated in osteoclastogenesis (26,27), a role for ERRα in mediating the effects of MYC on cell phenotype and metabolism has not been previously appreciated, and mechanisms by which ERRα promotes osteoclastogenesis are mostly unknown.…”
Section: Resultsmentioning
confidence: 99%